Gay men's experiences with prostate cancer: Implications for future research. (March 2020) - Hoyt, Michael A; Frost, David M; Cohn, Eric; Millar, Brett M; Diefenbach, Michael A; Revenson, Tracey A
Gay men's experiences with prostate cancer and its impact on health-related quality of life are poorly understood. This qualitative study explored gay men's experience with prostate cancer with a focus on the emotional, physical, and sexual impact of cancer; support needs; and healthcare interactions. Three semi-structured focus groups of gay men with prostate cancer were conducted. A conventional content analytic approach was used to identify six primary content areas that described poignant aspects of the men's experience with prostate cancer: minority stress, intimacy and sexuality concerns, impact on life outlook, healthcare experiences, social support and the gay community, and intersectional identities.